The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/pen.25707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of characteristic scale on the extrudate swelling behavior of polypropylene melt in a micro‐extrusion process

Abstract: The swelling behavior in micro‐extrusion has a significant effect on the dimensional and shape accuracy of microproducts. In this study, the effect of characteristic scale, defined as the gap of die land in an annular micro‐extrusion die, on the extrudate swelling behavior of viscoelastic melt is analyzed through numerical simulations and micro‐extrusion experiments. The results show that the swelling behavior displays an obvious dependence on the characteristic scale. An increase in the characteristic scale r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The gauge length was set at 50 mm. Consistent with previous studies 2,40,41 substantial differences were observed in the extrudate diameters for the different techniques and operating conditions, due to swelling differences 42 . Furthermore, previous research 2 revealed that at the same (set) processing temperature extrudates with larger diameters require additional time to cool down.…”
Section: Methodssupporting
confidence: 89%
“…The gauge length was set at 50 mm. Consistent with previous studies 2,40,41 substantial differences were observed in the extrudate diameters for the different techniques and operating conditions, due to swelling differences 42 . Furthermore, previous research 2 revealed that at the same (set) processing temperature extrudates with larger diameters require additional time to cool down.…”
Section: Methodssupporting
confidence: 89%
“…The effect of this variation in the PLA crystallinity during the sample preparation was neglected, as previous studies observed a marginal impact of the degree of crystallinity on the thermal conductivity [61]. Moreover, previous studies on the melting mechanisms in SSEs observed that small variations in the thermal conductivity have a neglectable impact on the solid bed profile (SBP) [21,38].…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…This is performed according to geometric and process parameters that can have a strong influence on the properties of the final parts [13][14][15][16]. In recent years, however, a growing number of AM applications introduced the use of single-screw extruders (SSEs) fed with polymer pellets [17][18][19][20][21]. The global term for such AM modifications is extrusion-based AM (EAM), complementary with conventional large-scale extrusion [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…These models are more complex, with more parameters to be determined than the traditional power‐law model. Liu et al [ 9 ] studied a micro‐extrusion of polypropylene (PP) process by means of experiments and simulations. Their model was reduced by using symmetry in order to save on computational costs (reinforcing the need for computational capabilities at an affordable cost).…”
Section: Literature Reviewmentioning
confidence: 99%